BGA substrate outgassing negative impact study on Cu wire bonding. Issue 2 (2nd May 2017) - Zhang, Hanmin; Hu, Ming; Wang, Zhijie; He, Qingchun; Ye, Denghong
Abstract : Purpose: The purpose of this paper is to attempt to study the failure mechanism of BGA (ball grid array) Cu wire bond ball lift and specifically focused on substrate outgassing's impact on Cu wire bonding quality and reliability. Design/methodology/approach: The Galvanic corrosion theory has been widely adopted in explaining the failure mechanism of Cu ball bond lift issue during reliability test or field application in the presence of moisture. In this study, ion chromatography was performed on BGA substrate halogen analysis. EDX (energy-dispersive X-ray spectroscopy) was also used to detect the contaminant's element at the bottom surface of a window clamp. Further FTIR (Fourier transform infrared spectroscopy) analysis verified that the contamination is from substrate outgassing during wire bonding. A new window clamp design proved effective in reducing the negative impact from substrate outgassing during wire bonding. Findings: The solder mask in a fresh substrate contains a chlorine element. The chlorine can be detected in the BGA substrate outgassing during wire bonding by FTIR and EDX analyses, which have a negative impact on the Cu wire bonding. The window clamp with a larger opening can reduce the negative impact of the Cu wire bonding from the BGA substrate outgassing. Research limitations/implications: Because of the limitation of time and resources, bonding pad surface contamination from substrate outgassing and its correlation with Cu bonding ball lift failure after reliability test will be studied in depth later. Originality/value: The BGA substrate outgassing has negative impacts on Cu wire bondability. A window clamp with a larger opening can reduce the negative impact from substrate outgassing.